Communication—Platinum Dissolution in Alkaline Electrolytes. Issue 14 (1st January 2016) - Wang, Zhongqi; Tada, Eiji; Nishikata, Atsushi
Abstract : Platinum dissolution under potential cycling in KOH electrolytes was studied using inductively coupled plasma mass spectrometry. The dissolution amount was found to increase with the upper potential limit and was comparable to that in acidic media. The dissolution behavior of a possible dominant Pt species in one potential cycle below 1.4 V (vs. RHE) was assessed by a channel flow double electrode method. Under potential cycling between 0.4 and 1.4 V, most of the Pt dissolution was found to originate from the reduction of Pt oxide.